INTEGRASI NILAI GOTONG ROYONG DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KABUPATEN TAKALAR - Gusliana, Sindy; Mira; Masrullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine and analyze the integration of gotong royong values in improving individual taxpayer compliance in Takalar Regency. The low tax ratio in Indonesia and the limited level of voluntary taxpayer compliance indicate the need for a culture-based approach in taxation policies. This research employed a quantitative approach with an explanatory research design. The population consisted of 93,204 individual taxpayers registered at the Tax Service, Extension, and Consultation Office (KP2KP) of Takalar Regency. Using purposive sampling based on Slovin’s formula, 100 respondents were selected, consisting of taxpayers aged 25–55 years who possessed a Tax Identification Number (NPWP). Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results showed that all indicators met convergent and discriminant validity requirements, while reliability testing indicated satisfactory construct reliability values. The inner model evaluation produced an R-square value of 0.631, indicating that 63.1% of taxpayer compliance could be explained by gotong royong values. Hypothesis testing revealed a T-statistic of 3.304 and a P-value of 0.001, confirming that gotong royong values have a positive and significant effect on individual taxpayer compliance. These findings emphasize the importance of integrating local cultural values into tax socialization and policy strategies to encourage higher taxpayer compliance.